The Effect of Fiscal Decentralization on Inflation in Iran: An Application of Panel Smooth Transition Regression Model - Ali Akbar Bajelan; Saeed Karimi Potanlar; Ahmad Jafari Samimi (مدلسازی اقتصادسنجی, 2017)
The aim of this study is to investigate nonlinear effects of fiscal decentralization on inflation in the Hybrid New Keynesian Phillips curve framework in Iran. To meet this end, using the data of 30 provinces during 2005 to 2012 and Panel Smooth Transition Regression (PSTR), the relationship between fiscal decentralization and inflation has been examined. The results show that the effect of fiscal decentralization on inflation is asymmetric and depends on the fiscal decentralization level; So that, by increasing the level of fiscal decentralization, the inflation rate was first reduced and then increased. The results of other parameters estimation also show that output gap, inflation lag and inflation expectations have a positive and asymmetric impact on the current inflation rate.